New Ecologies of the Real: Nonsimultaneity and Canadian Literature(s) - Siemerling, Winfried (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2016)
This essay draws attention to variations in the use of formal textual strategies that sometimes have been overlooked in the productive but potentially homogenizing shift from Canadian literature to Canadian literatures. A mere insistence on pluralization can run the risk of masking differences that include specific forms of “nonsimultaneity” or ungleichzeitigkeit (Ernst Bloch). Such differing relations to time—or heterochronicities— imply related, varying views of space, point to different functionalities of formal modes and genres, and influence how texts relate to audiences and intervene in the public sphere. I argue that the deployment of formal elements is often contingent on social dimensions and cultural specificity, and thus on contextual factors whose consideration was seen as detrimental to the discussion of Canadian literature in Frank Davey’s “Surviving the Paraphrase.” Focusing on examples drawn from black Canadian cultural expression, I examine contextually motivated temporalities in works by George Elliott Clarke, Marie-Célie Agnant, Sylvia Hamilton, Camille Turner, and Wayde Compton. By using distinct strategies of re-temporalization and re-spatialization, these writers and artists work towards the “not-yet” of a differently conceived future and exert civic agency with the help of formal choices in their art.